PENGARUH PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA STAFF DALAM KANTOR PT. RIAU MEDIA TELEVISI PEKANBARU) - Kesumawaty, Endang; Heriyanto,, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The research was conduscted in PT. Riau Media Televisi Pekanbaru. This studythe setting of the problem is the effect of the implementation of work controlling onemployee performance at PT. Riau Media Televisi Pekanbaru. Work controlling as anindependent variable (X) and employee performance achievement as the dependentvariable (Y), and this study took a number of respondents were 80 respondents. Dataobtained through the questionnaire and then further processed to be tested throughstatistical analysis such as a simple regression analysis, t test, and correlation analysisand determination with the help of using the SPSS 16 for windows application. Theresults prove that the implementation of work controlling to employee perfomanceachievementin PT. Riau Media Televisi Pekanbaru has done well.Keywords: Work Controlling, Employee Performance, Riau Media Televisi (Rtv)